Unfriending effects: Testing contrasting indirect-effects relationships between exposure to hate speech on political talk via social media unfriending. (December 2022) - Kim, Bumsoo; Wang, Yi; Lee, Janggeun; Kim, Yonghwan
Abstract: This study explores the antecedents and consequences of unfriending in social media settings. Employing an online panel survey ( N  = 990), this study investigates how exposure to hate speech is associated with political talk through social media unfriending. Findings suggest that social media users who are often exposed to hate speech towards specific groups and relevant issues are more likely to unfriend others (i.e., blocking and unfollowing) in social media. Those who unfriend others are less likely to talk about public and political agendas with those with cross-cutting views but tend to often engage in like-minded political talk. In addition, this study found indirect-effects associations, indicating that social media users who are exposed to hate speech are less likely to engage in cross-cutting talk but more likely to participate in like-minded talk via unfriending other users in social media. Highlights: Exposure to hate speech is positively associated with social media unfriending. Unfriending is positively related to like-minded political talk and negatively associated with cross-cutting discussion. Unfriending mediates the relationship between exposure to hate speech and political talk.